(3JfhjQ GdOjGLi aj JaSjQ GdCMGLjs - (3Yde GdOjf GdSNGhis; (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s ((3eMeO Hf YHO GdefYe Hf Ydi Hf YHO GdZfi Hf Ydi GdbQTi s)
(3ChdgG (B:s
(3GdMeO ddg Cf CTQM GdCMGLi GdJi hVYgG YdGeI ReGfg GdReNTQi hCf ChVM ZGeVgG s
(3BNQgG (B:s
(3djS gPG ef bHjd eG ai gPG GdcJGH aEf ajg ef GdeSGFd hGdahGFO eGdGjhLO eLehYkG ai cJGH s
(3COi hLhO GdQWhHI Edi eMh HYV GdcdeGJs
(3bhHdJ Ydi GdCUds
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs